Digital HR Practices and HR Innovation Driving Human Resource Management Transformation - Rumiris Siahaan; Willy Cahyadi; Limega Candrasa; Cia Cai Cen (Fundamental and Applied Management Journal, 2026)
Human Resource Management (HRM) transformation has become a strategic priority in regions facing digital disruption and economic restructuring. In North Sumatra, organizations encounter uneven digital readiness and workforce capability challenges, necessitating integrated HR approaches to enhance both organizational and regional performance. This study aims to examine the effects of digital HR practices and talent development on HRM transformation, to test the mediating role of HR innovation, and to assess the impact of HRM transformation on regional economic performance. A quantitative explanatory design was employed using a cross-sectional survey of 187 organizations across public, private, and MSME sectors in North Sumatra. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping (5,000 resamples).  The results indicate that digital HR practices (β = 0.312, p < 0.001) and talent development (β = 0.284, p < 0.001) significantly influence HRM transformation. HR innovation emerged as the strongest predictor (β = 0.337, p < 0.001) and partially mediated these relationships. Furthermore, HRM transformation has a strong positive effect on regional economic performance (β = 0.686, p < 0.001), with the model explaining substantial variance (R² = 0.61 for HRM transformation; R² = 0.47 for regional performance). The study concludes that HRM transformation in developing regions is driven by the integration of digital HR practices, talent development, and HR innovation. It extends digital HRM literature by demonstrating that HR transformation contributes not only to organizational effectiveness but also to regional economic competitiveness.